Surface electronic properties-driven electrocatalytic nitrogen reduction on metal-conjugated porphyrin 2D-MOFs - Maibam, Ashakiran; Orhan, Ibrahim B.; Krishnamurty, Sailaja; Russo, Salvy P.; BabaRao, Ravichandar (ACS Applied Materials and Interfaces, 2024)
Two-dimensional (2D) metal organic framework (MOF) or metalloporphyrin nanosheets with a stable metal-N-4 complex unit present the metal as a single-atom catalyst dispersed in the 2D porphyrin framework. First-principles calculations on the 3d-transition metals in M-TCPP are investigated in this study for their surface-dependent electronic properties including work function and d-band center. Crystal orbital Hamiltonian population (-pCOHP) analysis highlights a higher contribution of the bonding state in the M-N bond and antibonding state in the N-N bond to be essential for N-N bond activation. A linear relationship between Delta G(max) and surface electronic properties, N-N bond strength, and Bader charge has been found to influence the rate-determining potential for nitrogen reduction reaction (NRR) in M-TCPP MOFs. 2D Ti-TCPP MOF, with a kinetic energy barrier of 1.43 eV in the final protonation step of enzymatic NRR, shows exclusive NRR selectivity over competing hydrogen reduction (HER) and nitrogenous compounds (NO and NO2). Thus, Ti-TCPP MOF with an NRR limiting potential of -0.35 V in water solvent is proposed as an attractive candidate for electrocatalytic NRR.
Keywords: Density Functional Theory (DFT); electrocatalytic nitrogen reductionreaction; kinetic energy barrier; limitingpotential; Metalloporphyrin; NRR selectivity

Synthesis of Hofmann-based metal-organic frameworks incorporating a bis-pyrazole linker for various gas separations - Matthews, Brooke L.; Harvey-Reid, Nathan C.; Jangodaz, Elnaz; Scott, Victoria-Jayne; Polson, Matthew I. J.; Maibam, Ashakiran; BabaRao, Ravichandar; Telfer, Shane G.; Kruger, Paul E. (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: acetylene; C2H2/CH4; Ni; Purification; SPIN-CROSSOVER BEHAVIOR